EVALUATION OF LONGTERM OUTCOMES AFTER STROKE: RESULTS OF THE LIS-2 REGISTRY - C. Yu. Martsevich; N. P. Kutishenko; A. Yu. Suvorov; M. L. Ginzburg (Кардиоваскулярная терапия и профилактика)
Aim. To assess the results of long-term observation of the patients survived after acute stage of brain stroke or transient ischemic attack (ST/TIA) and discharged for outpatient care.Material and methods. The study was conducted based upon the registry of patients hospitalized with ST diagnosis in Lubertsy District Hospital №2 in 2009-2011 y. Totally, 960 persons included, inpatient died 207 (21,6%), 753 (78,4%) discharged for the continuation of outpatient care. In 2,8 years (2,1;3,5) after the discharge, life status of patients was checked, examination and instrumental study performed of the survived, and causes of death revealed for the dead.Results. Life status was updated for 688 (91,4%) patients.; died 237 (31,5%) persons, 374 (49,7%) patients were examined, 77 (10,2%) patients refused. Mean age of the examined — 72,0±8,9 y., in men — 70,2±8,5 y., in women — 72,2±9,9 y., women consisted ~2/3 of the total. Arterial hypertension was found in 91,7% patients, 2nd type diabetes — in 21,4%, atrial flutter of fibrillation — in 17,1%. In 3,5 years only ~50% survived amongst survivors of acute phase. Main cause of death — second ST (36,3%) and heart failure (22,4%), 67,6% of all lethal cases — cardiovascular and cerebrovascular diseases.Conclusion. The main causes of death at long term period in ST/TIA survivors are cardio- and cerebrovascular. Most patients died from second ST or cardiovascular complications, that dictates the need for improvement of secondary prevention system and rehabilitation of such patients and active implementation of evidence based medicine data to real clinical practice.